2019
DOI: 10.1021/acs.accounts.9b00397
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Death or Pro-Survival: Contrasting Paradigms on Nanomaterial-Induced Autophagy and Exploitations for Cancer Therapy

Abstract: Conspectus Autophagy is a critical lysosome-mediated cellular degradation process for the clearance of damaged organelles, obsolete proteins, and invading pathogens and plays important roles in the pathogenesis and treatment of human diseases including cancer. While not a cell death process per se, autophagy is nevertheless intimately linked to a cell’s live/die decision. Basal autophagy, operating constitutively at low levels in essentially every mammalian cell, is vital for maintaining cellular homeostasis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 77 publications
0
55
0
Order By: Relevance
“…Whether the involution of the mammary gland is normal or not will directly affect the collapse of the mammary duct and acinar structure and lactation performance. The unique physiological synthesis and secretion functions of mammary epithelial cells enable them to be used as an ideal model for the study of mammary gland bioreactor [6,7]. Thus, exploring the role of autophagy and apoptosis on the involution of mammary epithelial cells will undoubtedly be of great importance in productivity improvement of dairy animals.…”
Section: Introductionmentioning
confidence: 99%
“…Whether the involution of the mammary gland is normal or not will directly affect the collapse of the mammary duct and acinar structure and lactation performance. The unique physiological synthesis and secretion functions of mammary epithelial cells enable them to be used as an ideal model for the study of mammary gland bioreactor [6,7]. Thus, exploring the role of autophagy and apoptosis on the involution of mammary epithelial cells will undoubtedly be of great importance in productivity improvement of dairy animals.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the most noted autophagy-related cell death by NMs, nano-sized paramontroseite VO2 nanocrystals (P-VO2) were reported to induce cytoprotective autophagy in cultured HeLa cells (Zhou et al 2013). Furthermore, several NMs were also reported to induce pro-survival autophagy (Zhang et al 2019).…”
Section: Negative Turn-on Effect: Pro-survival Nature Of Autophagymentioning
confidence: 99%
“…Impaired autophagy is associated with lipofuscin accumulation in RPE cells [88,94]. Autophagy may perform pro-life and pro-death cellular functions and their regulation is not completely clear (reviewed in [95]). Mitter et al suggested that autophagy may be dysregulated in AMD in two ways depending on whether AMD-associated oxidative stress is acute (autophagy increased) or chronic (autophagy reduced) [94].…”
Section: Autophagymentioning
confidence: 99%